GAMBARAN POLA PERILAKU HIDUP SEHAT PADA MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Damayanti, Made Rini; Savitri Karin, Putu Ayu Emmy (Coping: Community of Publishing in Nursing, 2016)
Background: The time that students spend in a college is a transition period which bridging the developmental stage from childhood to adulthood. This period is characterized by their increasing sense of responsibility and autonomy for health. Student’s lifestyle will affect their lives in the future; it goes the same for nursing students. This may potentially affect their role in the future as a health promoter and a role model in health promotion. Objectives: To obtain the picture of lifestyle pattern of nursing students in Nursing Department Faculty of Medicine Udayana University. Methods: This study used descriptive cross-sectional design. Samples were active students of A and B programs in Nursing Department Faculty of Medicine Udayana University, both those are in academic and profession phases and met the inclusion criteria. The number of respondents from each class was determined based on the quota sampling technique. Data were collected using a fifty-two Likert scale questions from Health Promoting-Lifestyle Profile II (HPLP II) questionnaire that had been adapted into Indonesian language. Data were analyzed with descriptive statistic. Results : One hundred eighty nine questionnaires were collected back by respondents (87.91% respond rate). The scores of HPLP-II for all categories were in the range of 2.22 to 2.93. Spiritual development had the highest score (M =2.93, SD =0.38), meanwhile the value of physical activity had the lowest score (M=2.22, SD=0.42). Conclusion: Nursing students in Nursing Department Faculty of Medicine Udayana University have a relatively low healthy lifestyle scores and characterized by the dominance of HPLP-II scores below the average. Health promotion strategy that fits the needs and characteristics of nursing students is required. Furthermore, further research is needed to confirm the findings on this study.
Keywords: health promotion, health-promoting lifestyle, nursing students